Translation and Re-translation: The Memoirs of Eugénie de Montijo, Ex-Empress of France - Beal, Shelley (Mémoires du livre / Studies in Book Culture)

(untitled) (Groupe de recherche et d’étude sur le livre au Québec, 2010)
D. Appleton’s Memoirs of the Empress Eugénie, published in English in 1920 in New York and London and in translation in Denmark, Germany, The Netherlands and Sweden, took a circuitous path to publication since the completion of the manuscript in Paris in 1908. The widow of Napoléon iii had contributed via interviews with her godson, Comte Maurice Fleury, stipulating posthumous publication. To protect the work from copyright infringement in the interim, Fleury and co-editor Theodore Stanton translated the French manuscript material into English and added content. A clandestine, anonymous “pre-edition” produced in 1908 established D. Appleton’s claim in Great Britain and the United States. The European publishers, expecting a French manuscript, were dismayed at translating a translation, while re-translation of their versions into English posed the greatest threat to copyright. By 1920, the work’s autobiographical, first-person narration had been modified to the third person and Fleury’s name added as author, but not all European editions followed suit. A mismatched set of supposedly identical translations was the result.